2018
DOI: 10.1108/yc-07-2017-00713
|View full text |Cite
|
Sign up to set email alerts
|

Social comparison, materialism, and compulsive buying based on stimulus-response-model: a comparative study among adolescents and young adults

Abstract: Purpose The purpose of this paper is to provide the overview of factors responsible for materialism and compulsive buying among adolescents and young adults. In today’s world, materialism is a crucial phenomenon of the modern age. According to social comparison theory, comparisons are a significant factor affecting the behavioral intentions of adolescents and young adults. Thus, this study develops a framework based on the stimulus–organism–response model and uses the framework to examine the impact of interpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 103 publications
0
69
0
8
Order By: Relevance
“…At the highest levels of materialism, such possessions assume a central place in a person’s life and are believed to provide the greatest sources of satisfaction and dissatisfaction” (Belk, 1984, p. 291). Although Belk (1985) pointed out that materialism doesn’t necessarily relate to or led to negative outcomes, studies often focused on its role in undesirable behaviors/outcomes, such as compulsive buying (Islam et al, 2018), intention to buy counterfeit products (Furnham and Valgeirsson, 2007), and decreased level of psychological well-being (Christopher et al, 2009).…”
Section: Factors In the Conceptual Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…At the highest levels of materialism, such possessions assume a central place in a person’s life and are believed to provide the greatest sources of satisfaction and dissatisfaction” (Belk, 1984, p. 291). Although Belk (1985) pointed out that materialism doesn’t necessarily relate to or led to negative outcomes, studies often focused on its role in undesirable behaviors/outcomes, such as compulsive buying (Islam et al, 2018), intention to buy counterfeit products (Furnham and Valgeirsson, 2007), and decreased level of psychological well-being (Christopher et al, 2009).…”
Section: Factors In the Conceptual Modelmentioning
confidence: 99%
“…Concerns regarding the impact of social media influencers on adolescents’ psychological well-being and materialism have been increasing (Gritters, 2019; Stokel-Walker, 2019), it may be partly due to the fact that social comparison is ubiquitous on social media and it can lead to materialistic views (La Ferle and Chan, 2008). Recent research indeed revealed that social comparison with media celebrities positively correlates with adolescents’ materialism, which in turn, predicts compulsive buying (Islam et al, 2018). During this process, social media use moderated the relationship between social comparison and materialism, with increased social media use resulting in intensified materialism (Islam et al, 2018).…”
Section: Factors In the Conceptual Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Such kind of social comparisons empowered by social media and social networking sites raises materialism among youths and youthful grown-ups. Youths and youthful grown-ups discuss about their material gains with friends and get affected by the material possessions of celebrities; both are factors that promote materialism (Islam, Sheikh, Hameed, Khan, & Azam, 2018).…”
Section: Social Media Usage and Materialismmentioning
confidence: 99%
“…As per the study of Kamal, Chu, and Pedram (2013), social media usage is a significant predictor of materialism. Islam et al (2018) studied the impact of social media as a moderator between social comparisons with celebrities and materialism. They also studied the impact of social media as a moderator between social comparisons with peers and materialism and both hypotheses were significant and positive.…”
Section: Path Coefficientmentioning
confidence: 99%